What does effective allyship between social work and lived experience workers look like in the Australian forensic mental health context?. Issue 4 (2nd October 2021) - Lambert, Caroline; Egan, Ronnie; Thomas, Stuart DM
ABSTRACT: While forensic social work has a long history, it continues to struggle with its identity within a multidisciplinary team environment. Some jurisdictions have witnessed the development of informal partnerships between social work teams and lived experience workers, but little is known about their operation. Against this background, the aim of this project was to explore the presence, nature and operation of these partnerships in forensic mental health services. Social workers and lived experience workers from Australia and New Zealand attended a two-day summit to share practice-based experiences and engage in small group discussions. The Summit identified both a range of service models across forensic mental health services, and a keen interest in amassing practice-based wisdom to enable more formalised partnerships between social work and lived experience workers. Recommendations arising can be used as a platform to shape the future development and directions of allyship in forensic mental health practice.